Two-President Problem: Recognition of Head of State of Georgia after 29 December - Selkälä, Toni; Nikoleishvili, Shorena (Oxford University Press, 2026)
In recent months, Georgia has faced a deepening constitutional crisis. After elections marred with irregularities, the legality and legitimacy of the rule of the present powers-that-be have been questioned domestically and increasingly also internationally. These challenges to its authority have not barred the ruling party – Georgian Dream – from beginning parliamentary sessions as the sole party present and, consequently, nominating a government and electing a president. On the inauguration of the president elected by Georgian Dream, Mikheil Kavelashvili, on 29 December 2024, the predominantly domestic political crisis transformed into a matter of international concern. Salome Zourabichvili, Georgia’s fifth president, declines to recognize the legality of the parliament and, hence, the legality of Kavelashvili, allowing her to declare herself as the only legitimate president of the country. It is this two-president problem that has made domestic politics an international affair and recognition of a head of state a matter of interest.